Styles of educational Management and Institutional Climate in public IE in the district of Carmen de la Legua - Fasanando Guabloche, Rocio del Pilar (2018)
This article presents the most relevant conclusions of the research “Relationship between the style of educational management of managers and the institutional climate of public educational institutions in the district of Carmen de la Legua, this study is based on the analysis of the relationships of the variables style Educational Management and institutional Climate. The research methodological is Transactional type or transverse: Correlational. The purpose of this research is to know the type of Educational Management and its implication in the institutional climate. Which became known through statistical square CHI existence a significant association with a p_ value of 0.000 to 95% therefore the null hypothesis is rejected and generally accepted alternative which tells us that there is significant relationship between Management Style Educational Managers and Institutional Climate of Educational institutions of governance in the district of Carmen de la Legua.